2021
DOI: 10.3389/fendo.2021.684140
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Estrogen Receptors and GATA3 in Bladder Cancer: A Systematic Review and Meta-Analysis of Their Clinicopathological Significance

Abstract: BackgroundEstrogen receptors alpha (ERα) and beta (ERβ) and the cooperating protein GATA-binding factor 3 (GATA3) have been implicated in bladder carcinogenesis and tumour progression. GATA3 and ER have been functionally linked in the establishment of luminal fate in breast tissue, but to date their relationship in bladder cancer has not been established. This information will be useful to advance diagnostic and prognostic markers.AimTo determine the relationship between the expression of ERα, ERβ and GATA3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 118 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…GATA3, standing for GATA binding protein 3, contains two GATA-type zinc fingers at the structural level and is closely associated with the progression of various cancers, including breast cancer ( 8 , 32 34 ). GATA3 can also be considered a sensitive and specific marker for urothelial carcinoma ( 35 ) and as a criterion for BLCA subtypes classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GATA3, standing for GATA binding protein 3, contains two GATA-type zinc fingers at the structural level and is closely associated with the progression of various cancers, including breast cancer ( 8 , 32 34 ). GATA3 can also be considered a sensitive and specific marker for urothelial carcinoma ( 35 ) and as a criterion for BLCA subtypes classification.…”
Section: Discussionmentioning
confidence: 99%
“…Although GATA3 is highly expressed in bladder cancer, its high expression may adversely inhibit the progression of tumor cells in BLCA ( 6 ). Meanwhile, the over-expression of GATA3 predicts a lower tumor stage and a lower tumor grade but a higher relapse-free survival rate ( 7 , 8 ). Such an imbalance between the over-expression profile of GATA3 in BLCA cancer tissues and the inhibitory function of GATA3 on bladder cancer cells may be explained by the ability of GATA3 to transform basal bladder cancer cells into luminal cells ( 7 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression and accumulation of TP53 is then a predictor of poor prognosis in advanced-stage bladder tumors (49). TP53 expression has also been found to be associated with disease recurrence (50). Also, a meta-analysis suggested that overexpression of TP53 in NIMBC patients treated with BCG could be associated with RFS (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although the metastatic organs did not have typical cancerous nodes, tiny cancerous nodes were found under the microscope. Previous studies of the association between oestrogen and BC have demonstrated some mechanisms [ 41 , 42 ]. Moreover, the epidemiology of BC and related mechanical studies have confirmed the phenomenon and mechanism [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%